Inflation and counter-inflationary policy measures: The case of Hungary - Tamás Szemlér (Hans-Böckler-Stiftung, Institut für Makroökonomie und Konjunkturforschung (IMK), 2022)
Hungary has a history of high inflation rates. After the transformation period inflation reached up to 35% in the early 1990ies. Since then, economic policy measures contributed to signifi-cantly lower inflation and during the mid-2010s it was even close to zero. Inflation rates have begun to rise even before the war in Ukraine, however, the rise of inflation accelerated in 2022 leading to a (year-on-year) inflation rate (HICP) of almost 19% in August 2022. The rise in energy prices hit Hungarian households especially hard, since the government's "overhead reduction" program (a measure to shield households from the development of the energy prices introduced in 2013) had to be modified. Among the measures that were introduced to cushion the effects of inflation on households were various forms of price caps, e.g. for food prices, energy prices (electricity and gas, only up to a certain threshold) and fuel prices. Regarding the wage setting process one has to keep in mind that trade unions are rather weak in Hungary and only around one in five persons work at an establishment where a collective wage agreement is in place.
urn:nbn:de:101:1-2023011911222677221220
Keywords: 330; AK Wien; Hungary; Inflation; gas; electricity; price cap; HICP; energy; distribution; social pact; real wages